2019
DOI: 10.1002/ece3.4927
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical Bayesian approach for handling missing classification data

Abstract: Ecologists use classifications of individuals in categories to understand composition of populations and communities. These categories might be defined by demographics, functional traits, or species. Assignment of categories is often imperfect, but frequently treated as observations without error. When individuals are observed but not classified, these “partial” observations must be modified to include the missing data mechanism to avoid spurious inference. We developed two hierarchical Bayesian models to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
(121 reference statements)
2
6
0
Order By: Relevance
“…Our model results for age correction were consistent with the results from Samuel and Storm (2016). The pattern of age bias in adult females is consistent with known classification bias where adult females are over-placed in younger age classes (Ketz, Johnson, et al, 2019;Smith & McDonald, 2002). We also found that CWD status was the most important predictor of PRNP genotype for deer whose genotype was unknown (Table S6; Figure S5), and predictions were consistent with those from .…”
Section: F I G U R Esupporting
confidence: 87%
See 3 more Smart Citations
“…Our model results for age correction were consistent with the results from Samuel and Storm (2016). The pattern of age bias in adult females is consistent with known classification bias where adult females are over-placed in younger age classes (Ketz, Johnson, et al, 2019;Smith & McDonald, 2002). We also found that CWD status was the most important predictor of PRNP genotype for deer whose genotype was unknown (Table S6; Figure S5), and predictions were consistent with those from .…”
Section: F I G U R Esupporting
confidence: 87%
“…Moreover, under moderate antlered harvest, the proportion of 96GS/SS male fawns produced under high antlerless harvest was 4% higher than under low antlerless harvest, indicative of increased breeding success of 96GS/SS males. Correct age classification of wildlife species is notoriously difficult (Conn & Diefenbach, 2007;Ketz, Johnson, et al, 2019;Storm et al, 2014) and can affect epidemiological parameters (Lachish & Murray, 2018;Samuel & Storm, 2016;Storm et al, 2014). Our model results for age correction were consistent with the results from Samuel and Storm (2016).…”
Section: F I G U R Esupporting
confidence: 83%
See 2 more Smart Citations
“…In a seminal article on closed population modeling, Otis, Burnham, White, and Anderson (1978) allowed capture probability to vary by time, individual capture response (i.e., fear or attraction to trapping devices) and individual heterogeneity (individual covariates such as age or sex) and greatly motivated following closed population modeling efforts to date (for a good quick overview of parameter estimation approaches for these models see table 1 in Chao (2001)). More recent models have been developed to handle intricacies which can arise in CR studies such as missing classification data (Ketz, Johnson, Hooten, & Hobbs, 2019; Lasantha Premarathna, Schwarz, & Jones, 2018), individual mobility (Jensen, 1994), continuous time data (Becker, 1984; Wang & Yip, 2002; Yip, Xi, Chao, & Hwang, 2000), obtaining data from multiple sources or observers (El‐Khorazaty, 2000; Givens et al, 2015) as well as interesting examples outside of wildlife sciences (Bucholz & Laplante, 2009; Weller, Hoeting, & von Fischer, 2018).…”
Section: Introductionmentioning
confidence: 99%